New Investigation of Old Well-logs and Core Samples in a Natural CO2 Occurrence. (July 2017) - Szamosfalvi, Ágnes; Zilahi-Sebess, László; Király, Csilla; Jobbik, Anita; Szalai, Zoltán; Falus, György
Abstract: The purpose of this study was to investigate the results of re-interpreted old well-logs and porosity and permeability measurements of core samples from a natural CO2 occurrence in NW-Hungary. The reservoirs formed in Neogene sediments over a basement high. We compared the estimated physical properties based on well logging and the results of core sample analysis. The goal of our investigation was to give a distribution of hydrogeological properties in the in Mihályi –Répcelak area. We outlined the paleoenvironment of the reservoirs and caprocks searching for the explanation of the formation of this natural CO2 storage.